Evidence for the Important Role of Oxidative Stress in the Pathogenesis of Acne: - Kardeh, Bahareh; Kardeh, Sina; Moein, Seyed Arman; Namazi, Mohammad Reza (Galen Medical Journal, 2019)
Acne vulgaris is a common inflammatory skin disorder which is recognizable by dermatological lesions and scars. In addition to some pathogenetic factors such as hyperkeratinization, upregulated sebum secretion, and immunoinflammatory reactions, recent studies have also connected oxidative stress to the pathogenesis of acne vulgaris. In this article, we will briefly review clinical studies that interrogated alterations in oxidative stress biomarkers by a systematic search conducted in PubMed, Web of Science, and Scopus using “acne”, “oxidative stress”, and “reactive oxygen species” keywords. Overall, studies have shown that oxidative biomarkers (e.g. lipid peroxidation final products) are higher in acne vulgaris lesions. A significant positive correlation has also been noted between acne severity and oxidative biomarkers. In contrast, diminished levels of antioxidant enzymes (e.g. superoxide dismutase and catalase) have been observed in acne. We propose four probable mechanisms for the role of reactive oxygen species (ROS) in acne pathogenesis. We believe that ROS can contribute significantly to the acne vulgaris pathobiology via toll-like receptor (TLR), peroxisome proliferator-activated receptor (PPAR), mTOR pathway, and innate immune system, resulting in inflammation by alterations in the generation of several proinflammatory cytokines including IL-1, IL-8, and TNF-α.